(untitled) (Baghdad Science Journal, 2007)
This research consists of the synthesis of some Schiff bases as ligands, the following type of ligands: (2-hydroxy-benzylidene)- thiourea = (L1) (2-hydroxy-benzylidene)- urea = (L2) The complexation of these ligands with some transition metal ions (Zn+2, Cd+2, Hg+2) was prepared. The Schiff bases with their corresponding prepared transition metal complexes have been characterized on the bases of their (C.H.N) elemental analysis, IR, UV-VIS, atomic absorption, the molar conductivity measurement and melting point. The structural geometries of complexes were suggested in solid state.